Key techniques in orthopaedic surgery - Stern, Steven H., 1958-; Saltzman, Matthew D.; Bono, Christopher M. (Thieme, 2018)
Key Techniques in Orthopaedic Surgery, 2nd Edition, by Steven Stern, Matthew Saltzman, and Christopher Bono provides a fully updated, easy-to-follow orthopaedics reference. The book encompasses a full spectrum of core orthopaedic procedures impacting pediatric to adult patients. Unlike dense orthopaedic tomes, the straightforward, streamlined approach makes this reference the ideal operating room companion. For each of the 60 procedures, the authors include numbered, step-by-step guidance. This is augmented with more than 300 high-quality black and white line drawings illustrating techniques